Identifikasi penyebab penyakit busuk bulir bakteri pada tanaman padi (Oryza sativa) dan pengendaliannya menggunakan isolat Bacillus spp. secara in vitro - Isnaeni, Siti Juli; Masnilah, Rachmi (Jurnal Proteksi Tanaman Tropis, 2020)
Bacterial grain rot disease in rice plant is a new disease in Indonesia. The disease can reduce rice production up to 40% in severe disease attack. Morphological and physiological identification of these pathogens can be useful as a strategy of disease control. Control of this disease using Agent Biological Control is a right step and eco-friendly. The research was conducted in July until November 2018 at Plant Quarantine Laboratory of Agricultural Quarantine Center Surabaya. Design of experiment used on pathogenic identification is descriptively and analytically while in strategy of diseases control used are Randomized Complete Design method of single factor as many as 5 treatment of Bacillus spp. such as; Ba1: Bacillus spp. isolate 1, Ba2: Bacillus spp. isolate 2, Ba3: Bacillus spp. isolate 3, Ba4: Bacillus spp. isolate 4, and Ba5: Bacillus isolate spp. 5. Research result showed that the pathogen causing bacterial grain rot in Rice is Burkholderia glumae with bacterial characteristic are Gram negative, aerobic, not fluorescent on Kings B medium, mesophyll, isotonic, can hydrolysis arginine and can produce enzyme of gelatinase and (2) Bacillus spp. Isolate which consistent to inhibiting B. glumae in vitro is Ba-1 with a mean inhibition of 17.88 mm and a variety of resistance mechanisms, namely bacteriostatic and bactericidal Isolate of Bacillus spp Keywords: Bacterial grain rot rice; Bacillus spp; Burkholderia glumae